БЮРОКРАТИЧЕСКОЕ ПРЕДСТАВИТЕЛЬСТВО В МНОГОНАЦИОНАЛЬНОМ СООБЩЕСТВЕ КЕНДАРИ В ПЕРИОД С 2007 ПО 2017 ГГ. - Эрни Комария; Энда Сетьовати; Джамалуддин Хос; Сартоно; Аминуддин; Абдул Кадир (Вопросы государственного и муниципального управления, 2024)
Local government personnel is expected to implement a merit-based staffing system. Therefore, this research aims to compile a model of regional staffing system according to the conditions of Kendari City people using a thinking method. Data was collected through questionnaires, observations, and interviews with high, middle, and low officials in Kendari City government. The data was analyzed using Coyle's Dynamic System Analysis, whichincludes problem recognition, understanding and system description, qualitative analysis, simulation modelling, as well as policy testing and design. The resultsshow that the management of regional personnelis inefficient due to tribal elements. Therefore, bureaucratic representation enables local wisdom to create a conducive performance atmosphere in impacting harmonization of social life.